Society 5.0 and Education 5.0: A Critical Reflection - Vieira, R.; Monteiro, P.; Azevedo, G.; Oliveira, J. (2023 18th Iberian Conference on Information Systems and Technologies (CISTI), 2023)
Society 5.0 and Education 5.0 are concepts that have emerged in recent years, which are related to the development of a society based on digital technology to build a more inclusive, fairer, and more sustainable world. The necessary conditions must be created for an environment that promotes not only technological innovation but also human well-being. The technological development achieved in recent years has brought with it great changes in the communication and relationship of people with the environment, and this means a clear understanding that the organization of society is changing and, as such, changing the educational system is off primary importance. Education 5.0 is born through this new conjuncture. This article is the result of a literature review on this topic, but mainly it is intended to be a critical reflection, raising issues that we believe deserve the attention of the scientific community, governments, industry, and the stakeholders.